precio e ingreso y su incidencia en la demanda de telefonía móvil en la ciudad de Riobamba. año 2015. - Villacrés Espín, Lupe Margoth (2017)
The present research makes an analysis about price and its incidence in the demand of mobile telephony in Riobamba city and the impact caused by it in the income of the price of the citizens. The work was developed in 4 chapters. In chapter I, a reference framework, the problem statement is developed, the objectives guiding the research, and the justification and importance of the study are made known. In Chapter II, the theoretical framework is developed, which supports the entire research process. The chapter is divided into 5 parts: Price, where it is studied, definition, price theory, price objectives, strategies, elements, stages and policies to set a price; In the second part, income is studied, emphasizing in the definition, at the origin of the income distribution, the approaches that generate income distribution. In the third part a study of the demand is made; in the fourth, the elasticity study is analyzed. Finally, an analysis is made of mobile telephony in Ecuador, such as active line numbers, legal framework, types of plans, tariffs or tariff ceilings. Chapter III, denominated methodological framework, the methods, type and design of the research, population and sample and the techniques used to collect the data and to process the information are presented. In the section, analysis and discussion of the results, we analyze the results obtained in the surveys conducted to the heads of household of the city of Riobamba, on aspects such as the need to acquire a mobile device with all the services that an operator offers, In order to maintain efficient communication with the rest of the world. Chapter IV outlines the conclusions and recommendations that have been obtained after the study.